Identification of the QTL underlying the vitamin E content of soybean seeds. (30th January 2017) - Liu, Huancheng; Cao, Guanglu; Han, Yingpeng; Jiang, Zhenfeng; Zhao, Hongwei; Li, Wenbin
Abstract: Vitamin E (VE) is an important antioxidant supplement for human health. Soybean seed extracts are the main source of VE supplements. Therefore, increasing the VE content of soybean seeds is important issue in breeding programmes. To detect quantitative trait loci (QTL) associated with VE in soybean seeds, 238 F6:7 recombinant inbred lines (RILs) were created by crossing a high VE cultivar, 'Beifeng 9', with a low VE cultivar, 'Freeborn'. A genetic map was constructed using 218 polymorphic simple sequence repeat (SSR) markers. Composite interval mapping analysis detected 66 QTLs for contents of individual and total VE, 21 for α‐tocopherol, seventeen for γ‐tocopherol, thirteen for δ‐tocopherol and fifteen for total VE. The QTLs were located on chromosomes 9, 10, 15, 18 and 19. Phenotypic variance underlain by each QTL ranged from 2.4% to 32.6%. Two major QTLs (BARCSOYSSR_10_1140–BARCSOYSSR_10_1188 and BARCSOYSSR_15_0855 to BARCSOYSSR_15_0887) associated with α‐Toc, γ‐Toc, δ‐Toc and total VE contents were mapped on chromosomes 10 and 15. They explained 12.0% and 32.6% of phenotypic variance for α‐Toc; 5.5% and 13.0% for γ‐Toc; 6.6% and 23.6% for δ‐Toc; and 19.6% and 21.8% for total VE. QTL intervals BARCSOYSSR_15_0790–BARCSOYSSR_15_0855 (Qα15_1, Qγ15_1), BARCSOYSSR_15_1113–BARCSOYSSR_15_1159 (Qα15_3, Qδ15_2, QTVE15_4) and BARCSOYSSR_15_1159–BARCSOYSSR_15_1190 (Qα15_4, Qγ15_5, QTVE15_5) were associated with α‐Toc and explained 22.2%, 23.8% and 24.4% of the phenotypic variation in multiple environments. BARCSOYSSR_09_1098–BARCSOYSSR_09_1128 (QTVE9_1) and BARCSOYSSR_15_0887–BARCSOYSSR_15_0935 (QTVE15_2, Qγ15_3) associated with total VE content explained 21.8% and 16.4% of the phenotypic variation in two environments. These QTLs allow for marker‐assisted selection for cultivars with high VE contents.